Innovative Development of Zhuang Excellent Traditional Culture in the Era of Integrated Media - Liu, Xiaoxiao; Li, Jing (CV. AFDIFAL MAJU BERKAH, 2024)
Chinese culture represents the rich tapestry of various ethnic traditions. The development of these diverse cultures is essential for the overall prosperity of Chinese civilization. Therefore, promoting the innovative advancement of the Zhuang ethnic group's traditional culture can bolster their cultural confidence, preserve the diversity of Chinese culture, strengthen national identity, foster ethnic unity and progress, enrich spiritual and cultural life, and support rural community development. In today's rapidly evolving integrated media landscape, driven by information technology, the innovative development of the Zhuang's traditional culture encounters significant opportunities. In this study, we first explored the value foundation of innovative development of excellent traditional culture of the Zhuang ethnic group in the era of integrated media. Then, we analyzed the promoting effect of integrated media technology on the innovative development of excellent traditional culture of the Zhuang ethnic group in the new media ecological environment. Finally, we summarized how to fully utilize new technological means, create an integrated media matrix, and leverage resource integration advantages to achieve innovative development of excellent traditional culture of the Zhuang ethnic group. The research results are conducive to deeply exploring the contemporary value of excellent traditional culture of the Zhuang ethnic group and activating its cultural vitality, continuously promoting the creative transformation and innovative development of excellent traditional culture in China, thereby promoting the prosperity and development of cultural undertakings and cultural industries.